Fear of Missing Organisms (FOMO): the discordance among broad-spectrum empiric antibiotic therapy, microbiologic results, and definitive antibiotic therapy for diabetic foot infections and lower extremity osteomyelitis - Morgan K. Morelli; Andrea H. Son; Yanis Bitar; Michelle T. Hecker (Cambridge University Press, 2023)
Abstract Objective: Empiric broad-spectrum antibiotic therapy is commonly prescribed for patients hospitalized with diabetic foot infections (DFI) and lower extremity osteomyelitis (OM). The primary objective was to evaluate the concordance between empiric antibiotic therapy, microbiologic results, and definitive antibiotic therapy with a focus on methicillin-resistant Staphylococcus aureus (MRSA) and resistant gram-negative organisms. The secondary objective was to evaluate the negative predictive values (NPV) of select risk factors for MRSA and resistant gram-negative organisms for microbiologic results with these organisms. Design: Retrospective cohort study. Setting: Safety-net health system in Ohio. Patients: Adults hospitalized and receiving antibiotic therapy for DFI or lower extremity OM in 2021. Results: For 259 unique patients, empiric therapies with activity against MRSA and resistant gram-negative organisms were administered to 224 (86.5%) and 217 (83.8%) patients, respectively. Definitive therapies with activity against MRSA and resistant gram-negative organisms were administered to 91 (35%) and 74 (28.6%) patients, respectively. Of 234 patients with microbiologic testing, 29 (12.4%) had positive cultures with MRSA and 41 (17.5%) with resistant gram-negative organisms. The NPVs of risk factors for MRSA and resistant gram-negative organisms for the absence of these organisms in culture were 91% and 85%, respectively. Conclusions: For patients hospitalized with DFI and lower extremity OM, our data suggest opportunities for substantial reductions in empiric therapies with activity against MRSA and resistant gram-negative organisms. The absence of risk factors for these organisms was reasonably good at predicting negative cultures with these organisms.